Prevalence, diagnostic delay and economic burden of endometriosis and its impact on quality of life: results from an Eastern Mediterranean population - Swift, Bethan; Taneri, Bahar; Becker, Christian M.; Basarir, Hasan; Naci, Huseyin; Missmer, Stacey A.; Rahmioglu, Nilufer (Oxford Univ Press, 2024)
Background There are limited data on endometriosis from the Eastern Mediterranean region. This study for the first time estimates the prevalence and impact of endometriosis on women in Northern Cyprus, an under-represented region in Europe.Methods Cyprus Women's Health Research Initiative, a cross-sectional study recruited 7646 women aged 18-55 in Northern Cyprus between January 2018 and February 2020. Cases were identified using self-reported and ultrasound data and two control groups were defined, with (n = 2922) and without (n = 4314) pain. Standardized tools, including the 11-point Numerical Rating Scale and the Short Form 36 Health Survey version 2, were used to assess pain and quality of life, respectively.Results Prevalence and median diagnostic delay of endometriosis were 5.4% [95% confidence interval (CI): 4.9-5.9%, n = 410] and 7 (interquartile range 15.5) years. Endometriosis cases experienced a higher prevalence of bladder pain compared with asymptomatic pain controls (6.3% vs. 1.0%, P < 0.001) and irritable bowel syndrome relating to pelvic pain compared with symptomatic (4.6% vs. 2.6%, P = 0.027) and asymptomatic (0.3%, P < 0.001) controls. The odds of endometriosis cases reporting an anxiety diagnosis was 1.56 (95% CI: 1.03-2.38) higher than the symptomatic and 1.95 (95% CI: 1.30-2.92) times higher than the asymptomatic controls. The physical component score of the health-related quality-of-life instrument suggested a significant difference between the endometriosis cases and the symptomatic controls (46.8 vs. 48.5, P = 0.034). Average annual economic cost of endometriosis cases was Int$9864 (95% CI: $8811-$10 917) including healthcare, costs relating to absence and loss of productivity at work.Conclusion Prevalence was lower than the global 10% estimate, and substantial proportion of women without endometriosis reported moderate/severe pelvic pain hinting at many undiagnosed cases within this population. Coupled with lower quality of life, significant economic burden and underutilized pain management options, the study highlights multiple opportunities to improve care for endometriosis patients and women with pelvic pain.
Keywords: Work Productivity; Pain; Migraine